2023
DOI: 10.1097/won.0000000000000971
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictive Model of Medical Adhesive–Related Skin Injury in Cancer Patients Managed With Central Venous Access Devices

Abstract: PURPOSE:The purpose of this study was to determine the prevalence of medical adhesive-related skin injury (MARSI) at the site of central venous access device (CVAD) implantation in patients with cancer, identify risk factors associated with MARSI in patients with cancer, and create a nomogram for predicting risk of MARSI. DESIGN: Retrospective, single-center study. SUBJECTS AND SETTING:The sample comprised 1172 consecutive patients who underwent CVAD implantation between February 2018 and February 2019; their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…In 2017, the World Congress of Vascular Access defined central vascular access device (CVAD)-associated skin impairment (CASI) based on the definition of MARSI 2. A study of 1172 patients with cancer and CVAD placement found that 24.1% of CVAD sites had MARSI, and those with peripherally inserted central venous catheters (PICC) placement sites had a higher incidence of MARSI than those with other types of CVADs 3…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2017, the World Congress of Vascular Access defined central vascular access device (CVAD)-associated skin impairment (CASI) based on the definition of MARSI 2. A study of 1172 patients with cancer and CVAD placement found that 24.1% of CVAD sites had MARSI, and those with peripherally inserted central venous catheters (PICC) placement sites had a higher incidence of MARSI than those with other types of CVADs 3…”
Section: Introductionmentioning
confidence: 99%
“…2 A study of 1172 patients with cancer and CVAD placement found that 24.1% of CVAD sites had MARSI, and those with peripherally inserted central venous catheters (PICC) placement sites had a higher incidence of MARSI than those with other types of CVADs. 3 PICCs can be left in patient blood vessels for up to a year and are widely used in long-term cancer treatment; however, repeated application and removal of adhesive products during catheter maintenance can increase the risk of MARSI, particularly in patients with cancer…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation